2012
DOI: 10.1021/am201557k
|View full text |Cite
|
Sign up to set email alerts
|

Modulating Contact Angle Hysteresis To Direct Fluid Droplets along a Homogenous Surface

Abstract: The shape and motion of drops on surfaces is governed by the balance between the driving and the pinning forces. Here we demonstrate control over the motion of droplets on an inclined surface by exerting control over the contact angle hysteresis. The external modulation of contact angle hysteresis is achieved through a voltage-induced local molecular reorganization within the surface film at the solid-liquid interface. We show that tuning contact angle hysteresis alone is sufficient to direct and deform drops … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 45 publications
4
40
0
Order By: Relevance
“…For instance, Luo et al achieved electric-potential-driven droplet motion on an inclined substrate surface in air (Figure 5a). [62] The motion of the droplet could be controlled based on adjustment of the CA hysteresis by electric-potentialresponsive molecular reorganization at the solid-liquid interface. Tuček et al reported electric-field-controlled kerosenedroplet transport on a water surface containing surfactants.…”
Section: Electric-field-induced Directional Liquid Motionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Luo et al achieved electric-potential-driven droplet motion on an inclined substrate surface in air (Figure 5a). [62] The motion of the droplet could be controlled based on adjustment of the CA hysteresis by electric-potentialresponsive molecular reorganization at the solid-liquid interface. Tuček et al reported electric-field-controlled kerosenedroplet transport on a water surface containing surfactants.…”
Section: Electric-field-induced Directional Liquid Motionmentioning
confidence: 99%
“…This offers the possibility of creating liquid/ solid composite interfaces that are responsive to other stimuli for manipulation of immiscible liquids and other objects. [62] Copyright 2012, American Chemical Society. b) Directional motion of an oil droplet in water with cooperation of an electric field and a gradient microstructure.…”
Section: Magnetoresponsive Composite Interfacesmentioning
confidence: 99%
“…Contact angles and adhesion may also be altered through electrowetting, which causes a local voltage-induced molecular reorganization near the solid-liquid interface. 8 Such an approach can direct and deform drops when subjected to a constant external driving force such as gravity. 8 Theoretical simulations have shown that electrowetting can modify the shape of the liquidliquid interface between two dielectric liquids, yielding a fl uidic ratchet mechanism that can propel the fl uid.…”
Section: Fabrication and Synthesis Of Anisotropic Surfacesmentioning
confidence: 99%
“…8 Such an approach can direct and deform drops when subjected to a constant external driving force such as gravity. 8 Theoretical simulations have shown that electrowetting can modify the shape of the liquidliquid interface between two dielectric liquids, yielding a fl uidic ratchet mechanism that can propel the fl uid. 9 Engineered surfaces exist that change their wetting properties on command or in response to stimuli.…”
Section: Fabrication and Synthesis Of Anisotropic Surfacesmentioning
confidence: 99%
“…The largest potential-dependent change in contact angle is typically observed in the receding angle, where it is postulated that a surface will restructure only in the region of applied potential (wetted area), which will have a greater impact on the receding angle. 41 Advancing and receding contact angle values of aqueous 0.1 M KCl (pH 11) on either an LD-BMUA or an MUA monolayer were measured at different applied potentials. Five subsequent cycles between −0.1 and 0.290 V (vs Ag/AgCl) were measured and are provided in Figure 4.…”
Section: ■ Introductionmentioning
confidence: 99%